A Chirality/Light Dual‐Responsive Calixarene‐Functionalized Gold Surface for the Separation of Naproxen Enantiomers. Issue 7 (26th June 2019) - Xu, Pingping; Quan, Jiaxin; Chen, Wan; Zhang, Jin; Yan, Hewei; Liu, Yanxiang; Tan, Shiliang; Zeng, Xiangfei; Li, Haibing; Yang, Guangfu
Abstract: Chiral and photo‐responsive calix[4]arene ( trans CAC4) host system that can be adsorbed onto gold surfaces was rationally designed and produced in quantitative yields. Chiral recognition through strong host–guest interaction between trans CAC4 and ( R )‐naproxen was confirmed by fluorescence titration and 1 H NMR analysis. Functionalization of the gold surface with trans CAC4 was demonstrated by increased contact angle and XPS measurement. Photoswitching by trans‐cis isomerization of CAC4 and CAC4‐modified gold surfaces was confirmed by UV‐vis spectroscopy and contact angle experiments. Trans CAC4‐modified gold surfaces showed selective adsorption towards ( R )‐naproxen, while cis CAC4‐modified gold surfaces did not show any distinctive interaction with ( R )/( S )‐naproxen. Langmuir isothermal plots and LSCM studies proved quantitative adsorption of ( R )‐naproxen by the trans CAC4‐modified surface. This study demonstrated chiral recognition of a drug system by visual macroscopic changes, which may be used as a convenient methodology to separate bioactive enantiomers. Abstract : Efficient separation : A chirality/light dual‐responsive calix[4]arene‐modified gold surface can regulate the enantioselective adsorption of ( R )‐naproxen upon a macroscopic change through photoisomerization of an azobenzene unit. This result was confirmed by the dynamic contact angle, and the Langmuir‐isothermal plot confirmed quantitative adsorption of ( R )‐naproxen, which can be applied for convenient separation of naproxen enantiomers.